Pengaruh Iklan Dan Harga Terhadap Keputusan Pembelian Handphone Merek Xiomi Pada Ivan Cell Malang (Studi Kasus Pada Konsumen Ivan Cell Malang) - Moh. Halil; Agus Widarko; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
ABSTRACTThis study aims to determine the effect of advertising and price on purchasing decisions at Ivan Cell Malang. The sample in this study amounted to 80 respondents.The method used is descriptive data analysis by using the validity, reliability, normality test, multicollinearity test, heterocesdasticity test, multiple linear analysis test, determination coefficient test, f test, and t hypothesis test.The results of descriptive analysis in this study indicate that each variable has an effect on purchasing decisions, namely advertising, price has a positive effect on purchasing decisions. Advertising variables have a significant effect on purchasing decisions at Ivan Cell Malang Stores. Price variables have a significant effect on purchasing decisions at Ivan Cell Malang Stores. Advertising and price simultaneously influence purchasing decisions at Ivan Cell Malang Stores.Keywords: Advertising and Price Against Purchasing Decisions.